Annual Plan West Bengal 1994-95 Volume 2 - Planning Commission (Planning Commission, 1994)
This scheme envisages replacement and renovation of old machineries in a phased manner for improvement of working efficiencies of presses, decentralisation of Government Printing jobs and setting up of a DTP Press etc. No specific target is fixed for the scheme at present. A Technical Committee has been set up by the State Government to determine the programme and target in term of work out-put under the scheme.
Development and Planning Department Government of West Bengal
Development and Planning Department Government of West Bengal